Epidemiological characteristics of deaths related to surgical emergencies in Sub-Saharan Africa: case of Parakou, Benin - Allode, Alexandre S.; Hodonou, Adrien M.; Tamou-Sambo, Bio; Seto, Morel D. (International Surgery Journal, 2018)
Background: Emergency and resuscitation departments, often on the front lines of the hospital care system, are sadly the site of many deaths. Author aim to study the epidemiological characteristics of deaths related to surgical emergencies at Parakou Teaching Hospital in Benin. Methods: This was a prospective, descriptive study covering 6 months from January 1st to June 31st 2016. It focused on patients admitted to the emergency department and hospitalized in general surgery or resuscitation department during the study period. Three criteria were defined: admission for a surgical emergency, clinical classification of emergency patients (known as CCMU: Classification Clinique des Malades aux Urgences) between 1 and 5 and evolution marked by death. Results: A total of 54 deaths were recorded out of 379 surgical emergencies (14.2%). The sex-ratio was 2.2. The average age was 31±18.8 years old. The average admission time was 75.7±95.2 hours. The CCMU 4 and 5 were the most numerous (77. 7%). Traumatic emergencies were the most likely cause of death (56.6%), with cranio-encephalic trauma being the leading cause (38.9%). for non-traumatic emergencies (44.4%), acute generalized peritonitis is the leading cause of death (18.5%). The average time to surgical management was 87.4 hours, mainly related to the indigence of patients. Conclusions: The reduction of deaths related to surgical emergencies requires the adapted equipment of the different services involved in the care, the continuous training of staff and the creation of a health insurance.